Security competition by proxy: Asia Pacific interstate rivalry in the aftermath of the MH370 incident. Issue 1 (2nd January 2016) - Chong, Alan; Chang, Jun Yan
ABSTRACT: When Malaysia Airlines Flight MH370 disappeared from radar screens in the early hours of 8 March 2014, initial reactions suggesting that it was just another airliner disaster proved only partially correct. This article offers the interpretation that the multinational search effort for the missing Malaysian Boeing 777-200 airliner was revelatory of an abridged form of security competition among the mostly Pacific Rim states participating in both the post mortem and the search and rescue (SAR) operations. Although the Asia Pacific peace has been largely unbroken since the end of the Cold War, security competition among great powers, middle powers and weak states is still ongoing. In fact, this security competition is taking on proxy forms given the relative robustness of the overlapping architecture of Pacific Rim security regionalism in tamping down pressures for overt armed conflict to advance national security interests. MH370, following in the wake of the destruction wrought by natural disasters since the early 2000s, has provoked a competition in technological prowess in SAR operations, and more broadly, in quasi-civilian humanitarian assistance and disaster relief (HADR) capabilities amongst Pacific Rim states that have overlapping claims on the South China Sea and with interests in revising existing patterns of diplomatic order.